EFEKTIVITAS MIRROR THERAPY TERHADAP PENINGKATAN MOTOR SKILL EKSTREMITAS ATAS PADA KASUS STROKE : LITERATURE REVIEW - Aditya Denny Pratama; Mufida Zahra (LPPM Universitas Abdurrab, 2023)
Stroke is a neurological deficit that occurs suddenly caused by vascular disorders in the form of a lack of oxygen supply to the brain that lasts more than 24 hours, resulting in damage or necrosis of brain tissue. Clinical problems that are usually found include motor, language, sensory, cognitive and emotional disorders. One of the therapeutic methods that can be used to improve upper extremity motor skills in stroke patients is mirror therapy. The purpose of this study was to determine the effectiveness of mirror therapy to increase upper extremity motor skills in stroke cases. This study is a literature review study with a narrative method used. An evidence search was conducted on 5 databases, namely, Proquest, Scopus, Science Direct, Sage Publications and Taylor and Francis. The keywords used were â€œMirror Therapyâ€ AND â€œStrokeâ€ AND â€œUpper Limb OR Upper Extremityâ€ AND â€œMotor Skillâ€ with the inclusion criteria of full text articles, appropriate medical diagnosis and the last 5 years publication. There are 6 articles that will be reviewed. Based on a review conducted on 6 research articles, 4 of them stated that mirror therapy is effective for improving upper extremity motor skills in stroke patients with various parameters such as the upper extremity full-meyer assessment test (FMA-UE), action research arm test (ARAT). ), box and block test and wolf motor functional test (WMFT)